Experiments in small watershed response - Schulz, Edmund F., author; Yevjevich, Vujica M., 1913-, author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1972)
There is need in hydrologic research for a facility in which some of the many variables in the natural hydrologic system can be controlled or varied at will. Size or scale is an important consideration. Some of the design features of the CSU Experimental Rainfall-Runoff Facility are discussed especially those which have been modified. Three classes of experiments are described. Experiments dealing with the flow hydraulics in the sheet of overland flow have been used to verify the kinematic wave theory and to define the character of roughness and resistance to flow. A second group of experiments have studied the erosion caused by the overland flow. These have contributed some experimental data on the evaluation of channel systems and the nature of sheet erosion. The third group of experiments have provided some data on the pollution hazards of spent oil shale residues resulting from both rainfall and snowfall.
CER72-73EFS-VY12.
December 1, 1972.
Submitted to Office of Water Resources Research, U.S. Department of Interior.
The work upon which this report is based was supported (in part) by funds provided by the U.S. Department of Interior, Office of Water Resources Research as authorized by the Water Resources Research Act of 1964 and pursuant to Grant Agreement No. 14-31-0001-3264.
Keywords: Watershed management; Runoff -- Computer programs